Career Stress and Psychological Well-Being in Emerging Adulthood: The Moderating Role of Close Relationships - Erol, Sena; demir, ilkay; Atmacı, Kader; Battal, Elif Nur (My University, 2019)
Previous research linked career stress and poor amount of close relationships to negative psychological outcomes; however few studies focused on moderators in these relationships. The aim of the present study was to test the moderating role of family relations and romantic relationship status on the relationship between career stress and psychological well-being among emerging adults. Participants of the study were 270 university students (213 female; Mage=20,7; SD=2,1) from four universities in Istanbul. The Social and Emotional Loneliness Scale for Adults- Short Form (SELSA-S), PERMA-Profiler and a personal information form were used to collect the data. A three step hierarchical regression analysis was conducted in order to test the significance of the main and interaction effects in the model. The results of regression model revealed significant main effects of career stress, family relations, romantic relationship status and age on psychological well-being. Furthermore, results showed that family relations moderated the relationships between career stress and psychological well-being, while romantic relationship status yielded no significant interaction effects. In order to further examine the significant interaction effects in the model, a moderation analysis was conducted. The results indicate that less loneliness within the family, buffer the negative impact of career stress on psychological well-being.
Keywords: Career Stress; Romantic Relationships; Psychological Well-Being; Emerging Adulthood; Kariyer Stresi; Romantik İlişkiler; Psikolojik İyi Olma; Beliren Yetişkinlik